Impaired virtual space-tilting perception in Parkinson's disease with Pisa syndrome. (November 2022) - Sasaki, Fuyuko; Oyama, Genko; Hirozane, Yoshihiko; Yamashita, Ryo; Sekimoto, Satoko; Hattori, Nobutaka
Abstract: Introduction: The mechanism of Pisa syndrome in Parkinson's disease (PD) is unclear. We aimed to analyze the spatial perception of patients with PD with Pisa syndrome using virtual reality. Methods: In total, 16 patients with Pisa syndrome, 16 age-matched patients without Pisa syndrome, and 16 age-matched controls were included. They viewed the virtual room gradually tilting to different 8 directions randomized across trials. The 75% discrimination threshold angle and the mean tilting discrimination angle for each direction were evaluated. Participants' lateral trunk deviation was measured using Kinect. Neuropsychological status was evaluated, using the Mini-Mental Status Examination (MMSE), the Japanese version of the Montreal-Cognitive Assessment, Frontal Assessment Battery, and the color-word interference task of the Stroop test. Visuospatial abilities were assessed using Benton Judgement of Line Orientation, and vestibular function was evaluated using Subjective Visual Vertical (SVV). Results: The 75% discrimination threshold in the tilting discrimination angle was larger in all directions for those in the Pisa syndrome group compared to patients in the without Pisa syndrome group and those in the control group. There were significant differences between the three groups for Front-Right, Right, and Back. Patients with Pisa syndrome showed a significantly worse performance in these tests compared with controls and tended to have worse SVV performance compared with patients without Pisa syndrome. Conclusion: The present findings support the hypothesis of visuo-spatial disability and/or attentional impairment in patients with Pisa syndrome. Highlights: The virtual space-tilting perception was impaired in Parkinson's disease patients with the Pisa syndrome compared to patients without Pisa syndrome and controls. Visual-spatial function and/or attentional in patients with Pisa syndrome impaired.